2006
DOI: 10.3177/jnsv.52.183
|View full text |Cite
|
Sign up to set email alerts
|

Beef Extract Supplementation Increases Leg Muscle Mass and Modifies Skeletal Muscle Fiber Types in Rats

Abstract: SummaryThe objective of this research was to investigate the effects of beef extract on fat metabolism, muscle mass and muscle fiber types in rats. We also investigated the synergetic effect of endurance exercise. Twenty-four male rats weighing about 270 g were assigned to two diets containing 0 or 6% beef extract (BE). Half the rats fed each diet were subjected to compulsory exercise (CE) for 30 min every other day. After 4 weeks feeding, the blood was collected and various organs were dissected. The muscle f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
7
1
Order By: Relevance
“…In general, increased persistent muscle contraction leads to transition from fast-to-slow type fibers while decreased contraction leads to a slow-to-fast fiber type transition. Furthermore, hormonal status (particularly that of thyroid hormones [35] and of food components [23][36]) can also alter muscle fiber types. While these findings demonstrate that muscle fiber types can be readily altered, an efficient method for detecting this transformation did not exist.…”
Section: Discussionmentioning
confidence: 99%
“…In general, increased persistent muscle contraction leads to transition from fast-to-slow type fibers while decreased contraction leads to a slow-to-fast fiber type transition. Furthermore, hormonal status (particularly that of thyroid hormones [35] and of food components [23][36]) can also alter muscle fiber types. While these findings demonstrate that muscle fiber types can be readily altered, an efficient method for detecting this transformation did not exist.…”
Section: Discussionmentioning
confidence: 99%
“…The muscle fiber type in adult muscles can switch in response to hormonal status (particularly that of thyroid hormones) [ 8 ] or activation/contraction patterns, e.g., external electrical stimulation [ 9 ], paralysis due to spinal cord injury [ 10 ], denervation [ 11 ], cross-reinnervation (fast muscle reinnervated by a slow nerve and vice versa) [ 12 ], mechanical unloading [ 13 ], and food components [ 14 ]. Endurance training is also a well-known stimulus that induces fast-to-slow fiber type transition [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…9) Furthermore, it has been reported that beef extract supplementation and n-3 fatty acid intake changes the muscle fiber type from fast-twitch to slow-twitch. 10,11) In the animal experiments, muscle fiber type has been shown to be related to diabetes and obesity. 12,13) Modification of muscle fiber types is also reported in other fields such as sports nutrition and anti-aging.…”
mentioning
confidence: 99%